Identifikasi Dan Prevalensi Nematoda Saluran Pencernaan Pada Babi Lokal Di Kecamatan Satarmese Kabupaten Manggarai - Pratama, Leonardus E. P. C; Almet, Julianty; Djungu, Dewi F.L; Toha, Larry W.R (Jurnal Veteriner Nusantara, 2024)
Pigs are the most important type of livestock for small farmers in East Nusa Tenggara (NTT) Province. The Central Statistics Agency noted that pigs are the largest livestock population in East Nusa Tenggara. This study aims to indentify and determine the prevalence of intestinal worms in local pigs in the Satarmese sub-district, Manggarai regency. The samples used in this study were 82 samples of local pig faeces taken from breeders and were examined using the simple native method and the floating method and identified based on the morphology of the worm eggs. Based on the research results, it was found that the prevalence of gastrointestinal nematode infection in local pigs in the Satarmese sub-district, Manggarai regency, was 59% (48/82) with a prevalence in each village of 67% (Langgo Village), 45% (Iteng Village), 69% (Satar Loung Village), 58% (Koak Village) and 70% ( Tado Village). After identification, it was found that there were types of digestive tract nematode worms namely Ascaris sp, Strogloides sp, and trinchuris Sp.